Paradoks Metode Pembayaran Shopee: Studi Fenomena Konsumen COD yang Membayar melalui Transfer - Ratna Dyah Prabawati; Aszifa Salsabilla Arinda; Versiandika Yudha Pratama (STMIK Amika Soppeng, 2026)
This study aims to analyze the phenomenon of consumers who choose the Cash on Delivery (COD) payment method but make payments via transfer to the courier, a behavior that is inconsistent with the concept of COD and indicates a paradox in consumer decision-making. The study uses a descriptive qualitative approach with in-depth interview techniques with Shopee users who have practiced this method. The results show that the shift from cash to transfer payments is influenced by situational factors, perceptions of convenience, digital transaction habits, and the level of trust in couriers. Consumers choose COD to reduce the risk of fraud, but the practice of transfer payments has emerged because it is considered more practical, does not require cash, and is in line with m-banking habits. These findings indicate that perceived convenience is more dominant than perceived risk, thereby encouraging changes in payment behavior. This study concludes that this phenomenon reflects a shift in digital transaction culture that prioritizes flexibility and efficiency, while also highlighting the need for e-commerce payment systems to adapt to the growing trend of non-cash payment methods among consumers.